2019
DOI: 10.3390/w11091892
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Types of Small Hydropower Stations on Macroinvertebrate Communities in the Changjiang River Basin, China

Abstract: Many studies have investigated the influence of hydropower stations on macroinvertebrate communities, but few have clarified the influence of different types of hydropower stations. A total of 133 samples obtained from seven rivers, on which 45 hydropower stations are located, with the rivers distributed across four provinces (Yunnan, Jiangxi, Fujian, and Hubei) were investigated to study the influence of different types of small hydropower stations on macroinvertebrate communities. Samples were collected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As of 2015, over 47,000 small hydropower plants under 50,000 kW have been built in China. Most hydropower plants are located in the mountainous regions of southern China, where there are large reserves of water resources (rivers) [18]. According to [1], the average capacity of one small hydropower station was 143 kW.…”
Section: Fig1mentioning
confidence: 99%
“…As of 2015, over 47,000 small hydropower plants under 50,000 kW have been built in China. Most hydropower plants are located in the mountainous regions of southern China, where there are large reserves of water resources (rivers) [18]. According to [1], the average capacity of one small hydropower station was 143 kW.…”
Section: Fig1mentioning
confidence: 99%
“…The topographic variation is critical for maintaining species variety on floodplains, where a slight change in landform height affects seasonal flooding and plant distribution (Sparks, 1992). Flow persistence and substrate composition shape the community response to intermittent flows (Stubbington et al, 2009;Zhao et al, 2019). With time, flow management measures diminish river biota and in-channel habitat diversity.…”
Section: Response Of River Ecosystem To Fragmentationmentioning
confidence: 99%
“…Moreover, the biomass levels decreased. It was reported that the hydrological period was the main influencing factor and that the impact of the SHPs was not significant [84]. In this work, invertebrate studies in SHP reservoirs (low dams with clearly identified SHP types) were reviewed and systematized, concluding that the impact of small hydropower plant reservoirs and low dams is not clearly expressed for invertebrates, although the impact on more sensitive species was emphasized.…”
Section: Physico-chemical Quality Element Indicators In Watermentioning
confidence: 99%